Dimethyloxalylglycine lyophilized onto bone substitutes increase vessel area in rat calvarial defects. Issue 5 (6th September 2014) - Kuchler, Ulrike; Keibl, Claudia; Fügl, Alexander; Schwarze, Uwe Y.; Tangl, Stefan; Agis, Hermann; Gruber, Reinhard
Abstract Aim Pharmacological inhibitors of prolyl hydroxylases, also termed hypoxia‐mimetic agents (HMAs), when repeatedly injected can support angiogenesis and bone regeneration. However, the possible role of HMA loaded onto bone substitutes to support angiogenesis and bone regeneration under diabetic condition is unknown. The capacity of HMA loaded onto deproteinized bovine bone mineral (DBBM) to support angiogenesis and bone formation was examined in diabetic Wistar rats. Methods Diabetes was induced by intraperitoneal injection of streptozotocin. The HMA dimethyloxalylglycine (DMOG) and desferrioxamine (DFO) were lyophilized onto DBBM. Calvarial defects were created with a trephine drill and filled with the respective bone substitutes. After 4 weeks of healing, the animals were subjected to histological and histomorphometric analysis. Results In this report, we provide evidence that DMOG loaded onto DBBM can support angiogenesis in vivo. Specifically, we show that DMOG increased the vessel area in the defect site to 2.4% ± 1.3% compared with controls 1.1% ± 0.48% (P = 0.012). There was a trend toward an increased vessel number in the defect site with 38.6 ± 17.4 and 31.0 ± 10.3 in the DMOG and the control group (P = 0.231). The increase in angiogenesis, however, did not translate into enhanced bone formation in the defect area with 9.2% ± 7.1% and 8.4% ± 5.6% in DMOG and control group, respectively. No significant changes were caused by DFO. Conclusions The results suggest that DMOG loaded onto DBBM can support angiogenesis, but bone formation does not increase accordingly in a type 1 diabetic rat calvarial defect model at the indicated time point.